(untitled) (Al-Qamar, 2021)
Imam Hatip schools in Turkey have been considered a transformative Institute in the contemporary Muslim world due to their historical transformation and some unique characteristics. In the beginning, the sole objective of this system was to produce Imam and Hatip only. But, over time this aim was transformed to develop religious beliefs among the students. The objective of this article is to observe the historical transformation of this system as a significant fragment of the Turkish National Education System. Having grown continuously, Imam Hatip schools are now tasked with nurturing a new generation and special efforts are being made to certify these schools. So, their historical developments are evaluated and analyzed in this article.